Harmony concept of craniofacial morphology among the young Serbian population in Kosovo and Metohija - Djordjevic, Aleksandrija; Pavlovic, Jasna; Vukićević, Vladanka; Vujačić, Amila; SImić, Sanja; Martinović, Brankica (Vojnosanitetski pregled, 2022)
Background/Aim. Analyses of the cephalometric value of profile radiographs are very important for orthodontic diagnosis and planning of therapy. These values differ morphologically depending on ethnic and racial affiliation. The aim of this study was to confirm variations of cephalometric norms and the extent of their value and, according to them, confirm the harmony concept of craniofacial morphology among the young Serbian population in Kosovo and Metohija. Methods. This retrospective study comprised 183 profile radiograms of patients from Kosovo and Metohija, Serbia, aged 8–33, from which Class I was ascertained among 82 patients (53 female and 29 male). Five cephalometric angles were measured and analyzed. Pearson’s correlation coefficient was used to define the strength of correlation between the five variables. Bivariable linear regression was used to form harmonious combinations of individual values in the insight of craniofacial harmonious form. Multiple regression and standard error were used to form a harmonious schema. Results. Linear regression equations were used to define cephalometric floating norms. They helped us form a harmonious box and harmonious schema of craniofacial norms of the participants. The extent of harmonious value for orthognathic profile of our examinees varies for sella nasion subspinale (SNA) angle from 78° to 81°, for sella nasion supramentale (SNB) angle from 75.1° to 78.1°, for maxillary line – nasion sella line (NL-NSL) angle from 11.5° to 5.5°, for nasion sella basion (NSBa) angle from 134.7° to 125.8°, and for mandibulary line – nasion sella line (ML-NSL) angle from 40.5° to 30.6°. Conclusion. Cephalometric floating norms that describe the individual craniofacial pattern among the young Serbian population in Kosovo and Metohija, determined and defined by five cephalometric variables, and presented in the form of a harmonious box and harmonious schema and can accurately determine the craniofacial pattern.radiografija;